Analisis Reaksi Pasar Atas Pengumuman Peringkat Kinerja Perusahaan Dalam Pengelolaan Lingkungan Hidup - Trinadewi, Komang Winda; Wirawan Yasa, Gerianta (E-Jurnal Akuntansi, 2019)
This study aims to determine the market reaction to the PROPER announcement event and whether there are differences in market reactions between good ratings and poor PROPER ratings. This research is an event study with a window of events for 5 days. The study was conducted on PROPER participating companies listed on the Indonesia Stock Exchange from 2015 to 2017. The number of samples that met the criteria were 39 companies. PROPER announcements are measured using abnormal returns. The analysis technique used is the one sample t-test and the independent t-test. The test results show that the PROPER announcement was reacted negatively by the capital market, and there was no difference in market reaction between good ratings and bad ratings. Keywords : Event Study; Abnormal Return; Environmental Performance; PROPER.